Single sterile silicon ring technique for utilization of upper limb intravenous regional anesthesia: A prospective study of patients with operated distal radius fractures. Issue 12 (December 2021) - Kitridis, Dimitrios; Chalidis, Byron; Asouhidou, Irene; Koraki, Eleni; Givissis, Panagiotis
Highlights: Intravenous regional anesthesia is a well-established method of anesthesia in upper extremity surgery. The silicon ring tourniquet has been proved safe and effective when used as a conventional exsanguination and arterial occlusion device. Sterile silicone ring tourniquet application is a simple, safe and effective technique for internal fixation of distal radius fractures. Abstract: Introduction: Intravenous regional anesthesia is a well-established method of anesthesia in upper extremity surgery. In this study, we present a modification of the technique using a silicon ring tourniquet in 30 patients undergoing internal fixation for distal radius fractures. Methods: A sterile silicone ring wrapped within a stockinette sleeve was applied, and a local anesthetic solution (3 mg/kg lidocaine 0, 5%) was injected intravenously. After anesthesia onset, the ring was rolled distally to provide immediate pain and discomfort relief. Results: The silicone ring achieved adequate exsanguination in all patients. Mean pain VAS score was 2.7 ± 0.9 intraoperatively and 4.3 ± 1.3 during the first hour postoperatively. The onset and termination times of sensory block were 5.8 ± 2.1 and 102 ± 7.8 min, and of motor block 13.8 ± 2.8 and 54.2 ± 4.6 min, accordingly. All patients were satisfied from the procedure. Conclusion: Sterile silicone ring tourniquet application is a simple, safe and effective analgesic and anesthetic technique for the operative treatment of distal radius fractures.